Meilė Lukšienė through the Eyes of Young Researchers - Barkauskaitė, Marijona; Karužaitė, Daiva (Pedagogika, 2013)
Meilė Lukšienė, the initiator of Lithuanian education system reform, has named PhD students of education science as the hope for the further development of democracy process by doing everybody‘s job. The object of this research is the relation between young researchers and the ideas proclaimed by Meilė Lukšienė. The purpose of this article is theoretical and empirical revelation of the relation between young researchers and the ideas proclaimed by Meilė Lukšienė. Methods of the research include analysis of scientific literature of Meilė Lukšienė and about her; empirical quantitive research (case study) and statistical data analysis. The empirical research was carried out in 2013 and included 19 PhD students of education science from Lithuanian University of Educational Sciences.